(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses human lifespan problems and scientific research for their solution, methods of ageing problem research, a decrease in the adaptation of the organism in ontogenesis and the features of the metabolic state of adaptation strategies.